Synaptic plasticity in striatal function - Calabresi, Paolo (Henry Stewart Talks, 2014)
Basal ganglia circuits, Synaptic Plasticity and Striatal Neurotransmitters, Synaptic Plasticity and NMDA Receptors, Dopamine and Parkinson’s Disease, Dopamine Receptors and Striatal Neurons, Parkinson’s Disease and Levodopa-induced Dyskinesia